Forkhead box P3 regulatory T cells coexisting with cancer associated fibroblasts are correlated with a poor outcome in lung adenocarcinoma - Kinoshita, Tomonari (Cancer Sci, 2013)
Recently, an association between tumor infiltrating Forkhead box P3 regulatory T cells (T(reg)) and an unfavorable prognosis has been clinically shown in some cancers, but the mechanism of T(reg) induction in the tumor microenvironment remains uncertain. The aims of the present study were to examine the relationship between T(reg) and patient outcome and to investigate whether T(reg) induction is influenced by the characteristics of cancer‐associated fibroblasts (CAF) in lung adenocarcinoma. The numbers of T(reg) in both the tumor stroma and the tumor nest were counted in 200 consecutive pathological stage I lung invasive adenocarcinoma specimens. To examine whether the characteristics of CAF influence T(reg) induction, we selected and cultured CAF from low T(reg) and high T(reg) adenocarcinoma. The number of T(reg) was much higher in the stroma than in the nest (P < 0.01). Patients with high T(reg) had a significantly poorer prognosis than those with low T(reg) (overall survival: P = 0.03; recurrence‐free survival: P = 0.02; 5‐year overall survival: 85.4% vs 93.0%). Compared with the CAF from low T(reg) adenocarcinoma, culture supernatant of the CAF from high T(reg) adenocarcinoma induced more T(reg) (P = 0.01). Also, CAF from high T(reg) adenocarcinoma expressed significantly higher mRNA levels of transforming growth factor‐β (P = 0.01) and vascular endothelial growth factor (P = 0.01), both of which are involved in T(reg) induction. Our studies suggest the possibility that CAF expressing immunoregulatory cytokines may induce T(reg) in the stroma, creating a tumor‐promoting microenvironment in lung adenocarcinoma that leads to a poor outcome.